2020
DOI: 10.1039/c9ra10630h
|View full text |Cite
|
Sign up to set email alerts
|

Application of hyperspectral imaging for spatial prediction of soluble solid content in sweet potato

Abstract: Visible and near infrared (Vis-NIR) hyperspectral imaging was used for fast detection and visualization of soluble solid content (SSC) in ‘Beijing 553’ and ‘Red Banana’ sweet potatoes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 41 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…Based on the iPLSR for feature variable selection, machine learning methods including k-nearest neighbor (KNN) and PLSR models achieved better results in glucose prediction ( R 2 P = 0.88) compared with that in sucrose prediction ( R 2 P = 0.36) [ 129 ]. This imaging technique combined with SPA–SVR and CARS–MLR was capable of visualizing the spatial distribution of soluble solid content (SSC) in sliced sweet potatoes [ 80 ]. Moreover, total anthocyanin (TA) and moisture content in processed potato and sweet potatoes were detected during convective hot-air drying and microwave drying [ 51 , 94 ].…”
Section: Applications For Tuber Quality Assessmentmentioning
confidence: 99%
“…Based on the iPLSR for feature variable selection, machine learning methods including k-nearest neighbor (KNN) and PLSR models achieved better results in glucose prediction ( R 2 P = 0.88) compared with that in sucrose prediction ( R 2 P = 0.36) [ 129 ]. This imaging technique combined with SPA–SVR and CARS–MLR was capable of visualizing the spatial distribution of soluble solid content (SSC) in sliced sweet potatoes [ 80 ]. Moreover, total anthocyanin (TA) and moisture content in processed potato and sweet potatoes were detected during convective hot-air drying and microwave drying [ 51 , 94 ].…”
Section: Applications For Tuber Quality Assessmentmentioning
confidence: 99%
“…Mountrakis et al [ 56 ] also reported that SVR often produces higher accuracy than traditional methods because of its ability to handle small training datasets successfully. The SVR models performed better than the PLSR models in the quantitative determination of biochemicals, such as phosphorus in seafood [ 57 ], soluble solid content in sweet potato [ 78 ], and soluble solid content in Agaricus bisporus [ 79 ]. Ge et al [ 28 ] used Vis–NIR–SWIR to determine leaf physiological traits in maize, and the SVR model performed slightly better than the PLSR model for 5 traits.…”
Section: Discussionmentioning
confidence: 99%
“…The competitive adaptive reweighted sampling (CARS) algorithm and the successive projections algorithm (SPA) were used to filter the characteristic wavelength points related to the Brix to eliminate the irrelevant spectral data, reduce the computational effort and reduce the modeling time [31][32][33]. Fig 11 shows the results of the characteristic wavelengths selection using CARS, (a) the variation in the number of variables when different sampling times were selected, (b) the variation in the root mean square of cross-validation with the number of sampling times, and (c) a graph of the selection results of characteristic wavelengths using CARS.…”
Section: Characteristic Wavelengths Extractionmentioning
confidence: 99%